“I was trying to save the world”: delusion-like ideation and associated impacts reported by Western practitioners of Buddhist meditation - Solomonova, Elizaveta; Lindahl, Jared R.; Gold, Ian; Cooper, David J.; Little, Charlotte; Arteca, Damian; Cao, Chenxi; Britton, Willoughby B. (Frontiers in Psychology, 2025)
Delusional ideation is characteristic of psychopathology (e.g., psychosis, bipolar disorder) and is also found among the general population. Contemporary case studies have documented delusional ideation as a feature of meditation-induced psychosis, and Buddhist literature on the side effects and adverse effects of meditation also includes discussion of transient experiences that could be considered delusional or delusion-like ideation. Drawing upon interviews with more than 100 Buddhist meditation practitioners and meditation experts (teachers and clinicians) in the West, this paper presents a mixed-methods study of delusion-like ideation (DLI) associated with meditation. We establish a typology of eight types of DLI and report their relative frequencies among the sample; we identify impacts and treatment outcomes associated with DLI; and we provide four case studies that illustrate the risk factors, trajectories, outcomes, and appraisals associated with DLI. We show how responses to DLI are shaped not only by the type of DLI but also by their duration, severity, and impact, as well as the associated appraisals made both by meditators and by meditation teachers and psychiatrists. In some cases, the phenomenology of DLI suggests influences from the lived context of Buddhist meditation cultures. Furthermore, although DLI are normalized in Buddhist meditation culture under certain circumstances, meditation experts also noted the potential severity of meditation-related DLI, with some identifying it as a “red flag” meriting close monitoring if not immediate intervention. Finally, we discuss various explanatory models that could account for the presence, content, and impacts of DLI among meditators, drawing upon the environmental conditions and social contexts of meditation retreats, the role of attention and sensory attenuation in meditation practice, and the ways in which meditation-related DLI can function as a cultural and spiritual “idiom of distress.”